Velocity Loss as a Variable for Monitoring Resistance Exercise - González-Badillo, Juan José; Yañez-García, Juan Manuel; Mora-Custodio, Ricardo; Rodríguez-Rosell, David (International Journal of Sports Medicine, 2017)
This study aimed to analyze: 1) the pattern of repetition velocity decline during a single set to failure against different submaximal loads (50–85% 1RM) in the bench press exercise; and 2) the reliability of the percentage of performed repetitions, with respect to the maximum possible number that can be completed, when different magnitudes of velocity loss have been reached within each set. Twenty-two men performed 8 tests of maximum number of repetitions (MNR) against loads of 50–55–60–65–70–75–80–85% 1RM, in random order, every 6–7 days. Another 28 men performed 2 separate MNR tests against 60% 1RM. A very close relationship was found between the relative loss of velocity in a set and the percentage of performed repetitions. This relationship was very similar for all loads, but particularly for 50–70% 1RM, even though the number of repetitions completed at each load was significantly different. Moreover, the percentage of performed repetitions for a given velocity loss showed a high absolute reliability. Equations to predict the percentage of performed repetitions from relative velocity loss are provided. By monitoring repetition velocity and using these equations, one can estimate, with considerable precision, how many repetitions are left in reserve in a bench press exercise set.
Keywords: velocity-based resistance training; strength training; bench press; exercise prescription; muscle failure